Competition for pollination and isolation from mates differentially impact four stages of pollination in a model grassland perennial. (29th November 2020) - Richardson, Lea K.; Gallagher, M. Kate; Hayes, Tracie E.; Gallinat, Amanda S.; Kiefer, Gretel; Manion, Kristen; Jenkins, Miriam; Diersen, Greg; Wagenius, Stuart
Abstract: Species that persist in small populations isolated by habitat destruction may experience reproductive failure. Self‐incompatible plants face dual threats of mate‐limitation and competition with co‐flowering plants for pollination services. Such competition may lower pollinator visitation, increase heterospecific pollen transfer and reduce the likelihood that a visit results in successful pollination. To understand how isolation from mates and competition with co‐flowering species contribute to reproductive failure in fragmented habitat, we conducted an observational study of a tallgrass prairie perennial Echinacea angustifolia . We quantified the isolation of focal individuals from mates, characterized species richness and counted inflorescences within 1 m radius, observed pollinator visitation, collected pollinators, quantified pollen loads on pollinators and on Echinacea stigmas, and measured pollination success. Throughout the season, we sampled 223 focal plants across 10 remnant prairie sites. We present evidence that both co‐flowering species and isolation from mates substantially limit reproduction in Echinacea . As the flowering season progressed, the probability of pollinator visitation to focal plants decreased and evidence for pollen‐limited reproduction increased. Pollinators were most likely to visit Echinacea plants from low‐richness floral neighbourhoods with close potential mates, or plants from high‐richness neighbourhoods with distant potential mates. Frequent visitation only increased pollination success in the former case, likely because Echinacea in high‐richness floral neighbourhoods received low‐quality visits. Synthesis . In Echinacea, reproduction was limited by isolation from potential mates and the richness of co‐flowering species. These aspects of the floral neighbourhood influenced pollinator visitation and pollination success, although conditions that predicted high visitation did not always lead to high pollination success. These results reveal how habitat modification and destruction, which influence floral neighbourhood and isolation from conspecific mates, can differentially affect various stages of reproductive biology in self‐incompatible plants. Our results suggest that prairie conservation and restoration efforts that promote patches of greater floral diversity may improve reproductive outcomes in fragmented habitats. Abstract : Competition for pollination and isolation from mates may threaten successful pollination in species that persist in reduced and fragmented habitat. Using a model prairie perennial, we found that co‐flowering species richness and isolation from mates both impacted all four stages of the pollination process. Floral neighbourhoods with high pollinator visitation did not consistently exhibit successful pollination.